Climatic adaptation of Scots pine (Pinus sylvestris L.) in Finland based on male flowering phenology. - Luomajoki, Alpo (The Society of Forestry in Finland - The Finnish Forest Research Institute, 2009)
Timing of anthesis in 21 Scots pine stands from 14 localities in Finland was studied at the canopy level from 1963 to 1974. Distributions of pollen catches were compared to the normal Gaussian distribution. The basis for the timing studies was the 50 per cent point of the anthesis-fitted normal distribution. Development up to this point was characterized in calendar days, in degree days (>5 °C) and in period units. The count of each unit began on March 19 (included). The period unit was found to be the most accurate delineator of development both in a single year and also in the majority of cases as stand averages over several years. Locally, calendar days were a more accurate parameter for stand average. Anthesis in northern Finland occurred at a later date than in the south as was expected, but at a lower heat sum. The variation in the timing of anthesis and the variation of pollen catches increased northwards. The geographical correlations calculated against distances measured along simulated post-glacial migration routes were stronger than purely latitudinal correlations. Effects of the reinvasion of Scots pine into Finland are thus still visible in pine populations. The proportion of the average annual heat sum needed for anthesis grew rapidly above a latitude of 63° even though the heat sum needed for anthesis decreased towards the timberline. In light of flowering phenology it seems probable that the northern populations of Scots pine in Finland have still not completely adapted to the prevailing cold climate at these latitudes. A moderate warming of the climate would therefore be beneficial for Scots pine.